WALL-E - Newman, Thomas, 1955- (OSCAR : classic movies, 2008)
After hundreds of lonely years, a waste management robot finds a new purpose in life. With only a cockroach for a friend, he finds true love in another robot sent on a mission to Earth to see if it is safe for human life.